2022
DOI: 10.1371/journal.ppat.1010452
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functionally important domains of human cytomegalovirus gO that act after trimer binding to receptors

Abstract: Human cytomegalovirus (HCMV) entry involves trimer (gH/gL/gO) that interacts with PDGFRα in fibroblasts. Entry into epithelial and endothelial cells requires trimer, which binds unidentified receptors, and pentamer (gH/gL/UL128-131), which binds neuropilin-2. To identify functionally important domains in trimer, we screened an overlapping 20-mer gO peptide library and identified two sets of peptides: 19/20 (a.a. 235–267) and 32/33 (a.a. 404–436) that could block virus entry. Soluble trimer containing wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…However, it has been shown that gO null virus cannot enter epithelial cells, indicating that trimer is essential for entry into all cell types, including when PDGFRα is blocked (Zhou et al, 2015;Kabanova et al, 2016). Recently, functionally important domains of gO have been identified that function after receptor binding (Chin et al, 2022). The authors speculated on several models which included activation of gB for fusion.…”
Section: Stage 1: Viral Entry Into Host Cellsmentioning
confidence: 99%
“…However, it has been shown that gO null virus cannot enter epithelial cells, indicating that trimer is essential for entry into all cell types, including when PDGFRα is blocked (Zhou et al, 2015;Kabanova et al, 2016). Recently, functionally important domains of gO have been identified that function after receptor binding (Chin et al, 2022). The authors speculated on several models which included activation of gB for fusion.…”
Section: Stage 1: Viral Entry Into Host Cellsmentioning
confidence: 99%